Pengaruh Media Instagram Terhadap Minat Pembelian Kamar Pada Hotel Khas Pekanbaru Dengan Pemenuhan Informasi Sebagai Variabel Mediasi - zanra, sri wahyuni (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2023)
The purpose of this study was to determine the influence of Instagram media @khaspekanbaruhotel on the intention to purchase rooms at the Pesonna Hotel Pekanbaru with information fulfillment as a mediating variable. The population in this study were followers from the Instagram account @khaspekanbaruhotel and the sample in this study was 98 respondents. The results showed that Instagram media had a significant and positive effect on the intention to purchase rooms at the Pesonna Hotel Pekanbaru, Instagram media had a significant and positive effect on the fulfillment of information to respondents and the fulfillment of information to respondents had a significant and positive effect on the interest in purchasing rooms at the Pesonna Hotel Pekanbaru. In addition, it can be concluded that the fulfillment of information to followers is able to mediate the influence of Instagram media on the interest in buying a room at the Pekanbaru Specialty Hotel